GEOSPATIAL DYNAMIC OF VEGETATION COVER CHANGES ON THE SMALL ISLANDS, SOUTH SULAWESI, INDONESIA - AS, M. Akbar; Saleh, Buce; Sofian, Ibnu; Nurdin, Nurjannah (MAJALAH ILMIAH GLOBE, 2014)
ABSTRACTAgreement on the extent of mangrove forest in Indonesia has yet existed. The extent of mangrove forest in Indonesia 9 years ago was about 4.13 million ha. Currently, the mangrove has decreased significantly to 2.49 million ha (60%). Remote sensing could play an important and effective role for assessing and monitoring the dynamic of mangrove forest cover. The aim of this study is to measure the changes of the mangrove cover within 20 years period from 1993 to 2013, from 1993 to 2003, and from 2003 to 2013 using multi-temporal Landsat data. The study site was selected in Tanakeke Island, Takalar District, South Sulawesi, Indonesia. Results of the analyses show that the mangrove forest has decreased and it is caused anthropogenic impact.Keywords: geospatial dynamic, mangrove, remote sensing, GISABSTRAKSejauh ini belum ada kesepakatan mengenai luas hutan mangrove di Indonesia. Luas hutan mangrove di Indonesia 9 tahun yang lalu adalah sekitar 4,13 juta ha, akan tetapi sekarang menurun menjadi 2,49 juta ha (60%). Penginderaan jauh memiliki peranan penting dan efektif untuk penilaian dan pemantauan dinamika tutupan hutan mangrove. Tujuan dari penelitian ini adalah untuk mengukur perubahan tutupan hutan mangrove selama 20 tahun dari tahun 1993-2013, 1993-2003, dan 2003-2013, dengan menggunakan citra Landsat multi-temporal. Lokasi penelitian dipilih di Pulau Tanakeke, Kabupaten Takalar, Sulawesi Selatan, Indonesia. Hasil analisis menunjukkan bahwa luas hutan mangrove mengalami penurunan yang disebabkan oleh pengaruh dari manusia.Kata Kunci: dinamika geospasial, mangrove, penginderaan jauh, SIG